Discovery of a Biased Allosteric Modulator for Cannabinoid 1 Receptor: Preclinical Anti-Glaucoma Efficacy - Garai, Sumanta; Leo, Luciana M.; Szczesniak, Anna-Maria; Hurst, Dow P.; Schaffer, Peter C.; Zagzoog, Ayat; Black, Tallan; Deschamps, Jeffrey R.; Miess, Elke; Schulz, Stefan; Janero, David R.; Straiker, Alex; et al. (Journal of medicinal chemistry, 2021)
We apply the magic methyl effect to improve the potency/efficacy of GAT211, the prototypic 2-phenylindole-based cannabinoid type-1 receptor (CB1R) agonist-positive allosteric modulator (ago-PAM). Introducing a methyl group at the a-position of nitro group generated two diastereomers, the greater potency and efficacy of erythro, (+/-)-9 vs threo, (+/-)-10 constitutes the first demonstration of diastereoselective CB1R-allosteric modulator interaction. Of the (+/-)-9 enantiomers, (-)-(S,R)-13 evidenced improved potency over GAT211 as a CB1R ago-PAM, whereas (+)-(R,S)-14 was a CB1R allosteric agonist biased toward G protein- vs beta-arrestin1/2-dependent signaling. (-)-(S,R)-13 and (+)-(R,S)-14 were devoid of undesirable side effects (triad test), and (+)-(R,S)-14 reduced intraocular pressure with an unprecedentedly long duration of action in a murine glaucoma model. (-)-(S,R)-13 docked into both a CB1R extracellular PAM and intracellular allosteric-agonist site(s), whereas (+)-(R,S)-I4 preferentially engaged only the latter. Exploiting G-protein biased CB1R-allosteric modulation can offer safer therapeutic candidates for glaucoma and, potentially, other diseases.